Analysis of the Consistency Policy Indonesia's Capital Relocation in the Pandemic Era - Suswanta Suswanta; Danang Kurniawan; Achmad Nurmandi; Salahudin Salahudin (Jurnal Studi Sosial dan Politik, 2021)
This study aims to look at the narrative of public policies related to the relocation of the Indonesian capital in the era of the Covid Pandemic 19. The narrative is seen through the development of opinions of government policy actors, political parties, and society. This study uses a Q-DAS (Qualitative Data Analysis Software) approach; besides the data in this study are media and social media data. The media have an essential role to play in shaping public narratives related to policymaking. The role of public narratives can create collective awareness in providing information about actor choices in policy decision-making. This research will conduct a Narrative Policy Framework (NPF) study, which can describe, explain the structure of political narratives in policymaking. The results showed that the Government's attitude was inconsistent regarding relocating the State Capital (IKN) after the Covid 19 Pandemic. The policy choices made by the Government were evident from the Government's narrative that temporarily suspended the relocation of the State Capital (IKN). The policy steps taken by the Government are the impact of the developing public narrative related to the relocation of the State Capital (IKN) in the Covid 19 Pandemic era. The factors affecting budget availability are Covid 19, weak public support, regulations, and aspects of environmental damage. These factors have developed in the public narrative on mass media and social media so that the Government took steps to delay the process of moving the country's capital city (IKN).